Identification of Physical Activities in Post Stroke Patients - Titik Agustiyaningsih; Ollyvia Freeska Dwi Marta; Erma Wahyu Mashfufa (University of Muhammadiyah Malang, 2020)
Introduction: The incidence of recurrent strokes is increasing accompanied by the absence of intensive monitoring of physical activity that needs to be more addressed. The aims of intensively monitoring of physical activity to reduce disruption/ disability for life, to decrease the economic burden of the family, and to reduce the risk of death in stroke patients. Objectives: The purpose of this study was to determine the physical activity of patients after stroke attack. Method: We used an observational study design by case control approach, without giving certain treatment to the subjects of this study. We collected the demographic data from the participants and the International Physical Activity Questionnaire was used to measure the physical activity. The study was conducted at Aisyiyah Islamic Hospital in Malang, the average population was 30 people per month and samples were taken using purposive sampling technique. Data was collected by IPAQ questionnaire consisting of activities carried out around the house, activities at work and recreation activities and observation sheets. Results: The results showed that most physical activity of stroke sufferers was in the mild category (68.3%. Dicussion: It is recommended that respondents continue to do physical activity to reduce the prevalence of stroke recurrence.